Pengaruh Perilaku Konsumtif Terhadap Keputusan Pembelian Pakaian di Kebumen - Fitriani, Novi; Khasanah, Nur (EKONOMI DAN BISNIS DIGITAL, 2024)
This study aims to determine the influence of consumer behavior on clothing purchasing decisions in Kebumen. This study was conducted on the people of Kebumen Regency who buy clothes. Data collection was carried out by distributing questionnaires to 100 respondents. This study uses analytical techniques, namely descriptive and statistical analysis including validity tests, reliability tests, classical assumption tests, hypothesis tests and simple regression analysis. The software used is SPSS version 25 for windows. The results of this study indicate that consumer behavior variables have a significant effect on purchasing decisions with the results of the t test, namely the calculated t value> t table of 5.958> 1.98447 and a significance value of 0.000 <0.05 which states that the hypothesis is accepted.